1988
DOI: 10.1021/bi00415a025
|View full text |Cite
|
Sign up to set email alerts
|

Sequential dissociation of calcium from the calcium adenosinetriphosphatase of sarcoplasmic reticulum and the calcium requirement for its phosphorylation by ATP

Abstract: The kinetics for dissociation of the stable enzyme-calcium complex of the sarcoplasmic reticulum calcium ATPase, cE.Ca2, were followed by assay with simultaneous addition of [32P]ATP and EGTA, which gives 70% phosphorylation of cE.Ca2 with k = 300 s-1 (25 degrees C, pH 7.0, 5 mM MgSO4, 0.1 M KCl). The binding of ATP to cE.Ca2 is described by kATP = 1.0 X 10(7) M-1 s-1, k-ATP = 120 s-1, and Kdiss = 12 microM; ATP binding is partially rate limiting for phosphorylation at less than 100 microM ATP. The sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
71
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 51 publications
22
71
1
Order By: Relevance
“…We attribute these changes to ligand binding and conformational changes in the ATPase during the catalysis of Ca2 + -transport. This is supported by FTIR difference spectra of ATPase samples with caged ADP instead of caged ATP and of EGTA-inhibited [24] samples (data not shown). The transient absorbance changes of the 'normal' ATPase sample (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…We attribute these changes to ligand binding and conformational changes in the ATPase during the catalysis of Ca2 + -transport. This is supported by FTIR difference spectra of ATPase samples with caged ADP instead of caged ATP and of EGTA-inhibited [24] samples (data not shown). The transient absorbance changes of the 'normal' ATPase sample (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Acceleration of the rate of Ca 2ϩ dissociation in fact seems to be a fairly general feature of the effect of nucleotides, because it is observed at all Mg 2ϩ concentrations with both ADP and ATP␥S, the latter nucleotide being a poorly hydrolyzable analog of ATP probably resembling ATP more than AMPPCP does (23). As concerns ATP itself, detailed time-resolved phosphorylation experiments previously suggested also that the rate of Ca 2ϩ dissociation from Ca 2ϩ -ATPase was slightly enhanced (but not much) in the presence of Mg⅐ATP: Ca 2ϩ dissociation from the non-covalent E⅐Ca 2 ⅐ATP complex was estimated to occur with a rate constant in the range of 45-80 s Ϫ1 at 25°C and pH 7 in the presence of 100 mM KCl and 5 mM Mg 2ϩ (13), compared with 25 or 50 s Ϫ1 in the absence of ATP (depending on whether overall dissociation of the two Ca 2ϩ ions or dissociation of the most accessible one is considered) (34). Thus, under ordinary conditions, Ca 2ϩ dissociation does not appear to be blocked by the mere binding of nucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…All these models implicate that phosphorylation by ATP in the presence of Ca2+ proceeds through successive interdependent conformational changes [18,321, wereby the different binding domains shift relatively to each other. This further implicates possible changes of electrostatic interaction of the bound substrate with different amino acid residues during terminal Pi transfer and energy transduction.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…Due to the demands of the filtration method we had to determine ATP binding (binding of the nucleoside moiety) with non-saturating 10 pM [I4C]ATP or [32P]ATP (for kATp and Kd at pH 7.0 see [18]; for pH dependence, as all our experiments were performed at pH 6.15, see [19]). We still observed that ATP binding was less sensitive to SDS than covalent phosphorylation (Fig.…”
Section: Results a N D Discussionmentioning
confidence: 99%